WAQF ACCOUNTABILITY AROUND THE WORLD: A MINI-REVIEW - Ikhyanuddin, Ikhyanuddin; Raza, Hendra; Akhyar, Juni; Arief, Muhammad; Kusuma, Hidayah Dwi (UNISSULA, 2022)
This paper aims to review and understand about waqf accounting system in the world such as Asia, Europe, and African. The study of a review shows that a Waqf accounting system in Asia, Europe, and Africa has similarities, such as every country has a waqf institution for organizing waqf accounting (waqf asset, cash waqf, etc). Every country has its own way of regulating and operating waqf accounting. The growth of waqf in some minority countries is still constrained by several legal restrictions and the high cost of living in these countries.